Everything is tuberculosis [compact disc, unabridged] : the history and persistence of our deadliest infection - Green, John, 1977- (Penguin Random House Audio Publishing, 2025)
In 2019, author John Green met Henry Reider, a young tuberculosis patient at Lakka Government Hospital in Sierra Leone. In this book, John tells Henry's story, woven through with the scientific and social histories of how tuberculosis has shaped our world, and how our choices will shape the future of tuberculosis.